IMPROVING THE ABILITY TO UNDERSTAND MATHEMATICS LEARNING FOR MI THROUGH DISCOVERY LEARNING MODEL FOR PGMI STUDENTS - Ridania Ekawati; Yunardi Yunardi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The problem in this research was that PGMI students at UMSB found it difficult to understand Mathematics learning for MI. It was observed that the students did not participate actively and think creatively. This was indicated by the low participation in learning. This research objective was to improve the ability to understand mathematics learning at PGMI with Discovery Learning model. This research utilized qualitative and quantitative research methods with a type of Classroom Action Research. The research was conducted in 2 cycles for 2 meetings in each cycle. Data were collectedthrough pretest, posttest, observation, and interviews related to the learning process before and after implementing discovry learning model. The results of pretest revealed that 45% of students thought quite creatively while 50% of students thought less creatively, and only 5% of students thought very creatively. The first meeting in Cycle I was conducted through online discovery learning model with Zoom application and it was seen that 12.5% of students had a very high activeness level, 25% of students had high level of activeness, and 62.5% of students had moderate activeness. Then, the percentage of creative thinking was 67% and for less creative thinking was 25%, while 8% of students think very creatively. In Cycle II it was found that the level of students’ activeness increased to 17% for very high activeness; 67% of students had high level of activeness, and 16% of students had moderate activeness. Then, it was also found that 80% of students thought creatively and 20% of them thought very creatively. The increase in the average score and the average percentage of completeness indicated that the implementation of discovery learning model improved PGMI students’ understanding about mathematics learning for MI